2014
DOI: 10.2337/db14-0883
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide-1 Receptor Agonists Increase Pancreatic Mass by Induction of Protein Synthesis

Abstract: Glucagon-like peptide-1 (GLP-1) controls glucose homeostasis by regulating secretion of insulin and glucagon through a single GLP-1 receptor (GLP-1R). GLP-1R agonists also increase pancreatic weight in some preclinical studies through poorly understood mechanisms. Here we demonstrate that the increase in pancreatic weight following activation of GLP-1R signaling in mice reflects an increase in acinar cell mass, without changes in ductal compartments or β-cell mass. GLP-1R agonists did not increase pancreatic D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 41 publications
5
45
1
Order By: Relevance
“…Analysis of the protein expression profile in the mouse pancreas using tandem mass spectroscopy allowed us to deduce the identity of multiple proteins preferentially induced by GLP-1R agonists, including a subset of proteins important for protein translation. In contrast, we did not detect increases in abundance or activity of amylase or lipase (56). Whether these observations in mice are applicable to primates or humans remains unclear, and further work is needed to determine whether GLP-1 induces pancreatic protein synthesis in other species.…”
Section: Nonglycemic Pancreatic Actions Of Incretin Hormonescontrasting
confidence: 62%
“…Analysis of the protein expression profile in the mouse pancreas using tandem mass spectroscopy allowed us to deduce the identity of multiple proteins preferentially induced by GLP-1R agonists, including a subset of proteins important for protein translation. In contrast, we did not detect increases in abundance or activity of amylase or lipase (56). Whether these observations in mice are applicable to primates or humans remains unclear, and further work is needed to determine whether GLP-1 induces pancreatic protein synthesis in other species.…”
Section: Nonglycemic Pancreatic Actions Of Incretin Hormonescontrasting
confidence: 62%
“…A recent rodent study showed that incretin therapy increases pancreas mass by ~30% as a result of enhanced protein synthesis [99]. Although we have reported that there was no change in pancreas volume measured by CT scan 6 months after the initiation of liraglutide treatment [100], a slight increase in amylase or lipase after treatment with GLP-1RA has been consistently observed [100][101][102][103].…”
Section: Pancreatic Fat Beta-cell Function and Glucose Intolerancementioning
confidence: 48%
“…Using autopsy pancreas, Butler et al reported that pancreas mass was increased by ~40% in subjects with T2D who had been treated with incretinbased medicine [96], although these results may have been confounded by other factors [97,98]. A recent rodent study showed that incretin therapy increases pancreas mass by ~30% as a result of enhanced protein synthesis [99]. Although we have reported that there was no change in pancreas volume measured by CT scan 6 months after the initiation of liraglutide treatment [100], a slight increase in amylase or lipase after treatment with GLP-1RA has been consistently observed [100][101][102][103].…”
Section: Anti-diabetic Medication and Exocrine Pancreasmentioning
confidence: 99%
“…Circulating GLP-1 has two forms, GLP and GLP [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] amide. About 80% of circulating GLP1 in human is GLP [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] amide [18]. Plasma levels of GLP-1 in the basal level range between 5-10 pM and its level could increase to 50 pM after a meal.…”
Section: Glp-1mentioning
confidence: 99%
“…However, this efect is not caused by the increase in proliferation of islet or ductal cells. Increased protein synthesis in the exocrine acinar cells accounts for the increase of pancreas weight [24]. GLP-1 also inhibits glucagon secretion from pancreatic α cells after meals to lower the blood glucose.…”
Section: Glp-1mentioning
confidence: 99%